2018
DOI: 10.15585/mmwr.mm6732a3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Disabilities and Health Care Access by Disability Status and Type Among Adults — United States, 2016

Abstract: Persons with disabilities face greater barriers to health care than do those without disabilities (1). To identify characteristics of noninstitutionalized adults with six specific disability types (hearing, vision, cognition, mobility, self-care, and independent living),* and to assess disability-specific disparities in health care access, CDC analyzed 2016 Behavioral Risk Factor Surveillance System (BRFSS) data. The prevalences of disability overall and by disability type, and access to health care by disabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
368
4
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 600 publications
(435 citation statements)
references
References 7 publications
15
368
4
2
Order By: Relevance
“…Moreover, understanding the temporality between the various disabilities and the progression of severe COPD would be of particular importance as both the prevalence of COPD and disabilities are rising. [12,18] The available evidence has shown that the most common chronic conditions causing disabilities among adults are rheumatoid arthritis, spine problems, and cardiovascular disease. [20] However, these conditions increase in prevalence as the population ages, and do not fully explain the highest rates seen in the middle age group in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, understanding the temporality between the various disabilities and the progression of severe COPD would be of particular importance as both the prevalence of COPD and disabilities are rising. [12,18] The available evidence has shown that the most common chronic conditions causing disabilities among adults are rheumatoid arthritis, spine problems, and cardiovascular disease. [20] However, these conditions increase in prevalence as the population ages, and do not fully explain the highest rates seen in the middle age group in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…About one in four adults has a disability, including hearing, vision, cognition, mobility, self-care, and independent living. [12] Overall, mobility was the most prevalent disability type at 13.7%, followed by cognition, 10.8%, and independent living, 6.8%, hearing, 5.9%, vision, 4.6%, and finally self-care, 3.7%. [12] Income, region of residence, quality of accessible health services, and social determinants are all affecting the prevalence of these disabilities.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Age is intimately interwoven with disability (Barnartt, 2017;Zola, 1991). Old age is marked by an uptick in disability (Sommo & Chaskes, 2013), with 17% of those aged 18-44 years in 2016 reporting any disability versus 29% of those aged 45-64 years (Okoro, Hollis, Cyrus, & Griffin-Blake, 2018). With our cultural preferences for youth, non-dependence, and the idealized worker, the discrimination experienced by older people with disabilities is acute (Sheets, 2005).…”
Section: Disability Sexual Orientation and Agementioning
confidence: 99%